2020
DOI: 10.18632/aging.103444
|View full text |Cite
|
Sign up to set email alerts
|

Penehyclidine hydrochloride inhibits renal ischemia/reperfusion-induced acute lung injury by activating the Nrf2 pathway

Abstract: The nuclear factor (NF)-κB and NOD-like receptor protein 3 (NLRP3) pathways promote inflammatory signaling that injures the kidneys, whereas the nuclear factor erythroid 2-related factor 2 (Nrf2) pathway promotes anti-inflammatory signaling that inhibits oxidative damage. Penehyclidine hydrochloride (PHC) inhibits NF-κB and activates Nrf2 signaling. We investigated whether PHC induces communication between the Nrf2 and NF-κB/NLRP3 pathways, thereby protecting against renal ischemia/reperfusion (rI/R)-induced l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…PHC can alleviate pulmonary capillary spasm, improve local microcirculation, reduce edema, and inhibit the production of inflammatory mediators [138,139]. Previous studies have found that PHC could reduce renal ischemia/reperfusion-induced ALI, inhibit inflammation through the NF-κB pathway, and improve the leakage of pulmonary blood vessels in lung tissue [140]. In addition, PHC has been suggested to ameliorate severe pancreatitis-related acute lung injury (PALI) by inhibiting the expression of inflammatory factors [141,142].…”
Section: Penehyclidine Hydrochloride (Phc)mentioning
confidence: 99%
“…PHC can alleviate pulmonary capillary spasm, improve local microcirculation, reduce edema, and inhibit the production of inflammatory mediators [138,139]. Previous studies have found that PHC could reduce renal ischemia/reperfusion-induced ALI, inhibit inflammation through the NF-κB pathway, and improve the leakage of pulmonary blood vessels in lung tissue [140]. In addition, PHC has been suggested to ameliorate severe pancreatitis-related acute lung injury (PALI) by inhibiting the expression of inflammatory factors [141,142].…”
Section: Penehyclidine Hydrochloride (Phc)mentioning
confidence: 99%
“…Racanisodamine has been chosen as active control in several trials, and a response rate between 75.5% and 81.4% was found. 22,23 No additional intravenous fluid was administered in the first 60 minutes after acupuncture treatment.…”
Section: Interventionsmentioning
confidence: 99%
“…Whereas perioperative interventions, such as ischemic preconditioning, fluid management, and intermittent hemodialysis may reduce rI/R injury and AKI development in selected surgical patients, pharmacological approaches have so far yielded disappointing or mixed results [7,8]. Therefore, numerous preclinical studies, including our own, continue to explore both the specific contribution of innate immunity and potential approaches to restrict the inflammatory response, attenuate oxidative damage, modulate autophagy, and stimulate angiogenesis in the setting of rI/R injury [9][10][11][12][13].…”
Section: Agingmentioning
confidence: 99%